2019
DOI: 10.1111/jce.14269
|View full text |Cite
|
Sign up to set email alerts
|

Local impedance guides catheter ablation in patients with ventricular tachycardia

Abstract: Aims: Catheter contact and local tissue characteristics are relevant information for successful radiofrequency current (RFC)-ablation. Local impedance (LI) has been shown to reflect tissue characteristics and lesion formation during RFC-ablation.Using a novel ablation catheter incorporating three mini-electrodes, we investigated LI in relation to generator impedance (GI) in patients with ventricular tachycardia (VT) and its applicability as an indicator of effective RFC-ablation. Methods and Results: Baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…In our present study, a 15 Ω drop during RF correlated with effective lesions in left atrial tissue ablations, irrespective of the baseline voltage of the area. In two studies, 11,15 LI was reported to be a sensitive parameter for guiding RF ablation in patients with ventricular tachycardia (VT) when VT termination or loss of capture in the left ventricle was considered as ablation endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, a 15 Ω drop during RF correlated with effective lesions in left atrial tissue ablations, irrespective of the baseline voltage of the area. In two studies, 11,15 LI was reported to be a sensitive parameter for guiding RF ablation in patients with ventricular tachycardia (VT) when VT termination or loss of capture in the left ventricle was considered as ablation endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,19 Munkler et al demonstrated that the absolute LI drops were significantly greater at the effective ablation sites than ineffective sites during the VT ablation. 9 Martin et al demonstrated that the absolute and percentage LI drops were significantly greater at the successful lesions than unsuccessful lesions during ablation in the left atrium (LA) and ventricle. 11 The results of our study with a CTI ablation were consistent with that of those previous studies.…”
Section: Monitoring During Cti Ablationmentioning
confidence: 99%
“…Recent studies demonstrated that the LI provides valuable information on the catheter-tissue coupling and lesion formation during RF catheter ablation (RFCA), and a change in the LI during ongoing ablation is more sensitive than that in the generator impedance. [9][10][11] So far there have been limited studies evaluating the usefulness of LI monitoring during CTI linear ablation. Thus, the purpose of this study was to determine the optimal values of the LI drops for an effective RF ablation during an LI-guided CTI linear ablation.…”
Section: Introductionmentioning
confidence: 99%
“…When the ablation catheter (IntellaNav Mifi OI) was positioned at the corresponding location, the fragmented signals due to gap conduction into the veins were barely visible on ablation traces and were completely different from the Orion TM signals previously recorded at the same location (Figure 1, left panel), suggesting either that the catheter tip was not exactly on the gap, or that a large cancellation effect had occurred because of the wider field of view of the ablation electrodes than that of the Orion TM catheter one. [8] LI values at the same location showed an impedance value greater than 120 ohms (Figure 1, right panel), which was more compatible with the presence of surviving myocardial fibers in a gap region than with nearly unexcitable tissue, as suggested by signals on the ablation traces J o u r n a l P r e -p r o o f (LI values were around 88 ohms in the blood and around 95 ohms at lines of block in this patient). We applied RF energy and the veins became isolated when the LI drop reached 20 ohm (supplemental video 2).…”
Section: Case 1: Spotting a Gap In A Case Of Redo Pulmonary Vein Isolmentioning
confidence: 99%